Uma análise conforme a Constituição Federal do artigo 166 do CTN e sua incidência - Marquezi Junior, Jorge Sylvio (2011)
Given to the introduction of the article 166 of the National Tax Code, which occurred simultaneously with the advent of the same Codex in 1966, several discussions have been waged such as the constitutionality of the legal norm, the materiality of its incidence and, surely, the factual substance that give grounds to its application. As a result of these clashes, many interpretations emerged from the article in question. Unfortunately, most of them, although supposedly made within the bounds of our legal system, have pointed out with concepts from other branches of scientific knowledge, especially the financial one. This verity has restricted, as said by several doctrinaires, the interpretation of article 166 based on the concepts of direct and indirect taxes, as well as legal and taxpayer-in-fact. We are firm in saying that this nowadays understanding, indeed, is unconstitutional, although we see a possible analysis governed by the Federal Constitution. Believing that the existing interpretations were not sufficient to bring relief to the infamous legal device, mainly by the fact that carries by its side other branches of scientific knowledge, we propose in this work a brand new look, making a very clear and restricted methodological cut to the legal system and still, taking other paradigms for its analysis. We shall not only consider the tax view s itself, but also the taxpayers obligation, since he will assume the role of the subject to the unduly paid rule, exactly the time that the legal application s norm shall appear. For such analysis, we have as a foundation the Federal Constitution, with great emphasis on the principles of legality and property, which, in our understanding, are indispensable for the correct measurement of cases in which article 166 of the National Tax Code may appear. In short, grounded on the principles abovementioned and looking also to the taxpayer, we will explicit what is the correct interpretation of the article 166 by the terms of the Federal Constitution